2011
DOI: 10.1186/1476-072x-10-32
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor positive breast cancers and their association with environmental factors

Abstract: BackgroundEpidemiological studies to assess risk factors for breast cancer often do not differentiate between different types of breast cancers. We applied a general linear model to determine whether data from the Surveillance, Epidemiology, and End Results Program on annual county level age-adjusted incidence rates of breast cancer with and without estrogen receptors (ER+ and ER-) were associated with environmental pollutants.ResultsOur final model explained approximately 38% of the variation in the rate of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…One study suggested that ER+ case patients had higher DDE concentrations compared to controls 30 and a recent Environmental Protection Agency (EPA) report found that ER+ breast cancer was positively associated with proportion of agricultural land by county of residence. 31 Consistent with this, ever seeing a fogger truck at a residence prior to 1972 was associated with a higher odds of ER+PR+ tumors in the Long Island Breast Cancer Study Project (OR: 1.44; 95% CI: 1.08, 1.93). 9 However two other studies reported no difference in DDT concentration by hormone receptor status 32,33 and one report found varying associations between different organochlorine compounds and hormone receptor status.…”
Section: Discussionmentioning
confidence: 59%
“…One study suggested that ER+ case patients had higher DDE concentrations compared to controls 30 and a recent Environmental Protection Agency (EPA) report found that ER+ breast cancer was positively associated with proportion of agricultural land by county of residence. 31 Consistent with this, ever seeing a fogger truck at a residence prior to 1972 was associated with a higher odds of ER+PR+ tumors in the Long Island Breast Cancer Study Project (OR: 1.44; 95% CI: 1.08, 1.93). 9 However two other studies reported no difference in DDT concentration by hormone receptor status 32,33 and one report found varying associations between different organochlorine compounds and hormone receptor status.…”
Section: Discussionmentioning
confidence: 59%
“…Recent epidemiological literature indicates that risk factors for breast disease may differ according to hormone receptor expression and suggests that breast cancers stratified by hormone receptor status may represent etiologically distinct diseases with different clinical, pathologic, and molecular features . Likewise, the toxicokinetic properties of organochlorines have been hypothesized to be different based on clinical characteristics of the primary carcinoma, yet few studies have investigated these relationships in women with breast cancer and available data are inconsistent and contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hormones on mitochondria provides a possible link by which endocrine disrupting chemicals can influence the outcome of breast cancer and other diseases[164]. Of particular interest are estrogens that regulate glycolysis, the TCA cycle and OxPhos in a sex-specific specific manner [165].…”
Section: Host and Environmental Factors Affecting Mitochondrial Mementioning
confidence: 99%